New Nasopharyngeal Flap for Posterior Skull-base Reconstruction: The Upper-Tongue Flap - Pezato,Rogério (2022)
Abstract Introduction Reconstructions of clival resection are still challenging, and additional reconstructive methods may be necessary to achieve full coverage of the skull-base defect in patients with middle- and lower-clivus disease. Objective To describe a new nasopharyngeal flap for the middle and lower clivus. Methods Using nasal endoscopy in a cadaver dissection, we demonstrated a new nasopharygeal flap to cover the lower and middle clival resection. Results We described a new nasopharyngeal flap capable of covering the lower and middle portion of the clivus. Discussion The new nasopharyngeal flap, called the upper-tongue flap, is particularly adequate as an alternative for the reconstruction of middle and lower clivus defects, and it is better used in association with a nasalseptal flap in cases in which the nasalseptal flap alone does not provide enough mucosal coverage. Conclusion The new nasopharyngeal flap can be used in the reconstruction of clival resection.